A Brief Review on Text and Image CAPTCHA - Mahuya Sasmal, Palash Ray, Mrinmoy Sen,Rajesh Mukherjee, Shaon Bandyopadhyay (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Nowadays, security is a major concern and has garnered foremost attention in recent years as a result of the Internet's evident impact on all facets of human life. To provide an appropriate level of security, the Completely Automated Public Turing Test to Tell Computer and Human Apart, or simply CAPTCHA, has been designed for circumstances when bots must be prevented from performing a specific action, such as signing up and downloading. At the same time, it should be designed in such a way that people can execute the same action. Despite its many benefits, there are several major concerns about security, usability, and accessibility that make its use contentious. In this work, we attempted to provide a comprehensive analysis of many features and the state-of-the-art of CAPTCHA in general, as well as its alternatives in particular, to assist researchers in focusing on specific concerns to propose new solutions and ideas. With the advancement of CAPTCHA development, variousschemes of text-based and image-based CAPTCHAs have been described and compared. Furthermore, numerous proposed methods are used to classify and evaluate various sorts of CAPTCHA alternatives. This analysis could be useful in future studies aimed at developing new strategies for addressing current flaws.